Lower motor neuron facial palsy secondary to parotid abscess - first sign of uncontrolled diabetes mellitus: a case report - Ravunniarth, Lakshmi Menon; Kauser, Safina (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Facial paralysis associated with parotid disease is usually caused by a malignant process. Facial nerve palsy due to parotid gland abscess is very rare with only about 10 previously reported cases. Parotid abscess with facial palsy may be the first presenting symptom of underlying diabetes mellitus. We report a case of a 35-year-old man, not a known case of diabetes or hypertension, who presented with a right sided parotid abscess and difficulty in mouth opening with grade 4 facial nerve palsy, who on investigation was found to have underlying uncontrolled diabetes mellitus. Parotid abscess is mainly seen in elderly, diabetic and immunocompromised. Facial nerve palsy secondary to parotid abscess is a rare condition but probably underreported. Facial nerve palsy associated with parotid abscess is rare and may be one of the first presenting feature of uncontrolled diabetes mellitus.